2016
DOI: 10.21002/jepi.v17i1.632
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor Resiliensi Rumah Tangga Petani dalam Menghadapi Variabilitas Iklim

Abstract: Climate variability potentially giving shocks to farmers household. This research aims to identify farmers household vulnerability, identify factors affecting resilience, and identify the adaptation mechanism of farmers household in facing rainfall variability. The analytical methods are descriptive analysis, Livelihood Vulnerability Index, and multiple regression. Results shows that Sidamulya is more vulnerable than Wanasari. Households has low resilience. Factors that affecting resilience are education, earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
8
0
2
Order By: Relevance
“…Another study by Chamro & Widjayanthi (2020) found that fishermen in Puger, Jember are resilient during the lean season, during which fishermen can take advantage of their livelihood assets both in the livelihood system and in fishermen"s household assets. Marseva et al (2016) found that education level, income level from previous harvests, length of farming, and other dummy jobs affect the resilience of farmer households. Farmers adapt to survive by meeting their daily needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study by Chamro & Widjayanthi (2020) found that fishermen in Puger, Jember are resilient during the lean season, during which fishermen can take advantage of their livelihood assets both in the livelihood system and in fishermen"s household assets. Marseva et al (2016) found that education level, income level from previous harvests, length of farming, and other dummy jobs affect the resilience of farmer households. Farmers adapt to survive by meeting their daily needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…11 Selain itu, dalam penelitian Amalia tentang Analisis Faktor Resiliensi Rumah Tangga Petani dalam Menghadapi Variabilitas Iklim menyatakan bahwa pendapatan dari panen sebelumnya beperan dalam menentukan status kerentanan keluarga petani. 12 Adanya pandemi COVID-19 dapat memberi ancaman kehilangan pendapatan keluarga dan penurunan omset UMKM. Sehingga UMKM harus melakukan penjualan secara daring untuk memanfaatkan kesempatan dan menarik perhatian konsumen.…”
Section: Umurunclassified
“…The resilience of fishermen in facing climate change shows the ability of fishermen to respond, organize, learn and adapt to climate change. Households with low human, social and physical capital will have a low capacity to deal with climate disasters [2]. Wongke [2] also stated that most of fishing households have a low level of climate change resilience.…”
Section: Introductionmentioning
confidence: 99%
“…Households with low human, social and physical capital will have a low capacity to deal with climate disasters [2]. Wongke [2] also stated that most of fishing households have a low level of climate change resilience. The resilience of fishermen in facing climate change needs to be improved.…”
Section: Introductionmentioning
confidence: 99%